2017
DOI: 10.1039/c7ta06530b
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the photovoltaic thermal stability of fullerene bulk heterojunction solar cells through charge transfer interactions

Abstract: Charge transfer interaction of a donor polymer with an appropriate 9-fluorenylidene malononitrile derivative in the active layer leads to profoundly enhanced thermal stability of fullerene-based bulk heterojunction organic solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…It is envisioned that the solid‐state photoactive molecular mediator N(BAI) 3 may yield more stable device performance compared to the commonly used liquid‐state processing additives due to the absence of slow evaporation or migration of solvent additive residues in the bulk heterojunction films. In addition, it has been shown that multi‐armed molecules can facilitate the formation of a locked 3D mesh of donor polymer matrix through strong charge transfer interactions, resulting in enhanced thermal stability of devices by impeding the diffusion and aggregation of embedded PC 60 BM molecules . More comprehensive studies toward nanophase stability of the active layer and device stability are ongoing in our lab.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…It is envisioned that the solid‐state photoactive molecular mediator N(BAI) 3 may yield more stable device performance compared to the commonly used liquid‐state processing additives due to the absence of slow evaporation or migration of solvent additive residues in the bulk heterojunction films. In addition, it has been shown that multi‐armed molecules can facilitate the formation of a locked 3D mesh of donor polymer matrix through strong charge transfer interactions, resulting in enhanced thermal stability of devices by impeding the diffusion and aggregation of embedded PC 60 BM molecules . More comprehensive studies toward nanophase stability of the active layer and device stability are ongoing in our lab.…”
Section: Resultsmentioning
confidence: 94%
“…The volume fraction profiles were deduced from the data fits of the neutron reflectivity profiles shown in (a) as established in Ref. .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we measured the charge carrier mobility of optimized devices using the space-charge-limited current method. The device structures for hole and electron-only devices are glass/ITO/PEDOT/PSS/active layer/MoO 3 /Au and glass/Al/active layer/Al, respectively. , As shown in Figure a, the hole mobilities (μ h ) of TPDI-2P- and F-TPDI-2P-based blend films are 4.82 × 10 –5 and 8.76 × 10 –5 cm 2 V –1 s –1 , respectively, and the electron mobilities (μ e ) Figure b of TPDI-2P- and F-TPDI-2P-based blend films are 3.98 × 10 –5 and 6.82 × 10 –5 cm 2 V –1 s –1 , respectively, calculated from the slopes of J 1/2 – V curves. The higher μ h and μ e of the device based on F-TPDI-2P contribute to the improved J SC and FF values.…”
Section: Resultsmentioning
confidence: 99%
“…The enhanced interchain interaction is sensitive to the improved CT state at the donor/acceptor interface and the charge carriers’ transport progress. Previously, Spano et al reported that the interchain coupling and the degree of structural order can be reflected in the absorption ratio , of two peaks (shown in Figure f), whose intensities are denoted I 0–0 and I 0–1 , which are attributed to the transitions between the ground state and the first two vibronic levels of the excited state. The spectra, normalized at the 0–1 transition peak intensity to simplify the comparison of the relative 0–0 peak intensities, are shown in Figure f and can be used to evaluate the intrachain interactions of PTB7:PC 71 BM blend films. , The magnitude of the I 0–0 / I 0–1 ratio reflecting the size of the aggregate for PTB7:PC 71 BM:1% DDAB-sGO film is obviously higher than that for pristine PTB7:PC 71 BM film, while the 0–0 peak red-shifts slightly from 682 to 685 nm. We assume that this behavior is due to an increase in the size of the aggregates in the PTB7:PC 71 BM blend films.…”
Section: Resultsmentioning
confidence: 99%